Evaluation of Medication Errors in Prescriptions Pediatric Patients Are Reviewed from the Prescribing Phase - Elsa Mahardika Putri; Fendy Prasetyawan; Anis Akhwan Dhafin (International Journal of Global Sustainable Research, 2023)
Medication error is an error in the administration of drugs or the use drugs that endangers patients and is carried out by health workers, especially in terms of patient treatment services that can actually be prevented. The purpose of this study was to determine the percentage incidence of medication errors in the prescribing phases in the prescription of concoctions of pediactric patients. This study is a non-experimental study with an observational descriptive research design and the collection of prescription data using purposive sampling technique. The result of the research that has been carried out, the incidence of medication errors that most occur in the Sukorame Health Center Pharmacy Installation is in prescribing phase at 93%.